Teacher–student relationship moderates the association between tuberculosis close-contact exposure and somatic symptoms among adolescents in Hangzhou, China - Zijian Fang; Qingchun Li; Yinyan Huang; Qingjun Jia; Qinglin Cheng (Frontiers in Public Health, 2026)
Background Although tuberculosis (TB) control programs have primarily focused on infection prevention, diagnosis, and treatment outcomes, increasing attention has been directed toward the psychosocial consequences of TB-related experiences among affected populations. In school settings, adolescents identified as TB close contacts may experience concerns about infection risk, repeated health monitoring, activity restrictions, and disease-related stigma, which may represent important psychosocial stressors beyond the biological risk of infection. However, evidence regarding whether TB close-contact exposure is associated with somatic symptoms among adolescents remains limited. Methods A school-based cross-sectional study was conducted in Hangzhou, China, in April 2024. A total of 1,410 valid questionnaires were included (670 TB close contacts; 740 non-exposed students). Somatic symptoms were assessed using the Children’s Somatization Inventory-24 (CSI-24), and teacher-student relationship was evaluated using the Student-Teacher Relationship Scale (STRS). Binary logistic regression models were used to estimate associations, and interaction analyses were performed to evaluate whether the teacher-student relationship modified the association between TB close-contact exposure and somatic symptoms. Results A total of 169 adolescents (11.99%) were classified as having elevated somatic symptoms (ESS). The prevalence of ESS was significantly higher among adolescents with TB close-contact exposure than among non-exposed adolescents (14.78% vs. 9.46%, χ 2 = 8.925, p = 0.003). In univariate analysis, TB close-contact exposure was associated with increased odds of ESS ( OR = 1.659, 95% CI : 1.200–2.305, p = 0.002). After adjustment for sociodemographic characteristics and teacher-student relationship, the association remained significant (adjusted OR = 1.545, 95% CI : 1.105–2.167, p = 0.011). A 10-point increase in teacher–student relationship score was associated with lower odds of ESS ( OR = 0.861, 95% CI : 0.750–0.986, p = 0.032). Interaction analysis showed a significant interaction between TB close-contact exposure and teacher-student relationship (Per 10-point increase) ( OR = 0.577, 95% CI : 0.414–0.803, p = 0.001), indicating that the association between TB close-contact exposure and somatic symptoms differed according to teacher-student relationship quality, with a weaker association observed among adolescents reporting more positive teacher-student relationships. Conclusion Teacher-student relationship statistically modified the association between TB close-contact exposure and somatic symptoms. Adolescents reporting more positive teacher-student relationships showed a weaker association between TB exposure and elevated somatic symptoms. These findings suggest that the teacher-student relationship may represent an important school-based psychosocial factor associated with variability in adolescents’ responses to TB exposure. Given the cross-sectional design, the observed interaction should not be interpreted as evidence of a causal buffering effect. Longitudinal studies are needed to confirm these findings and determine whether school-based psychosocial support strategies can improve adolescent well-being during TB contact investigations.